Toleransi di indonesia: dinamika dan upaya penguatan dalam masyarakat multikultural - Mufid, Ainul (Maliki Interdisciplinary Journal, 2026)
Ethnic, linguistic, and religious diversity in Indonesia makes tolerance a crucial pillar for maintaining national unity. Although constitutionally guaranteed by Article 29 of the 1945 Constitution and the values of Pancasila, the practice of tolerance in Indonesia faces various challenges, particularly in the social, political, and educational domains. This article aims to comprehensively analyze the dynamics of tolerance in Indonesia, focusing on the concept of social psychology, influencing factors, local wisdom as a foundation, and the role of education in instilling tolerance values. This research employs a qualitative approach using the library research method, examining various relevant and freely accessible scientific sources. The findings indicate that tolerance is influenced by internal factors such as empathy and ethnic identity, as well as external factors including education, social interaction, social capital, and understanding of tolerance. Local wisdom, such as the Lonto Leok culture in West Manggarai, proves to be a strong foundation for the practice of tolerance that thrives in society. In education, strategies such as role modeling, heterogeneous group learning, habituation activities, and the implementation of religious moderation through intracurricular and extracurricular activities in madrasas contribute positively to the early development of tolerant attitudes. This article concludes that tolerance in Indonesia is a dynamic collective capacity that needs to be nurtured simultaneously through strengthening individual psychology and creating an inclusive social environment.